2022
DOI: 10.3390/ijms23179686
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Sensor REDD1 in Cancer and Inflammation: Friend or Foe?

Abstract: Regulated in Development and DNA Damage Response 1 (REDD1)/DNA Damage-Induced Transcript 4 (DDIT4) is an immediate early response gene activated by different stress conditions, including growth factor depletion, hypoxia, DNA damage, and stress hormones, i.e., glucocorticoids. The most known functions of REDD1 are the inhibition of proliferative signaling and the regulation of metabolism via the repression of the central regulator of these processes, the mammalian target of rapamycin (mTOR). The involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…In addition, hypoxia can also contribute to an immunosuppressive TME network 38 . Previous studies have reported DDIT4 as a downstream molecular target of HIF‐1a 12 . Upregulation of DDIT4 is also reported to potentially inhibit HIF‐1a through a negative feedback loop, reduce ROS levels and suppress tumorigenesis via a mTORC1‐independent pathway 42 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, hypoxia can also contribute to an immunosuppressive TME network 38 . Previous studies have reported DDIT4 as a downstream molecular target of HIF‐1a 12 . Upregulation of DDIT4 is also reported to potentially inhibit HIF‐1a through a negative feedback loop, reduce ROS levels and suppress tumorigenesis via a mTORC1‐independent pathway 42 .…”
Section: Discussionmentioning
confidence: 98%
“…DDIT4, also named as REDD1, is expressed under stress conditions, including oxidative stress, endoplasmic reticulum stress and hypoxia, and regulates the processes of cell proliferation, differentiation, and metabolism 11,12 . The major effect of DDIT4 is produced by inhibiting the cell‐growth regulator mTORC1, including serine/threonine kinases mTOR and mLST8, and raptor protein 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations